Glyciphon ointment for local treatment of basal cell cancer: clinical and pharmacological aspects - S. O. Podvyaznikov; A. M. Mudunov; A. V. Ignatova; D. A. Vasilkin; A. N. Anisimov; P. I. Shchennikov (Опухоли головы и шеи)
Introduction. Basal cell cancer (BCC) accounts for up to 80 % of all types of non-melanoma skin cancers. In 97 % of cases, BCC develops on bare facial skin, especially at the nose-forehead border, nose wings, corners of eyes and lips. Surgery can lead to gross cosmetic defects, therefore more and more specialists prefer conservative methods, among which local drug therapy holds a special place.The study objective is to evaluate the effectiveness and safety of glyciphon ointment for BCC local treatment as well as the economic costs. Materials and methods. The study included 114 patients who underwent BCC local drug therapy with 30 % Glyciphon ointment, where 111 (97.4 %) patients had primary BCC, and 3 (2.6 %) ones – recurrent BCC. Results. The study recorded 115 cases of use of glyciphon ointment in 114 patients. Doctors were fully satisfied with the treatment results in 101 (88.6 %) cases. In 11 (9.6 %) cases, satisfaction was partial due to severe adverse events (edema and hyperemia of the facial skin, pain), and in 2 (1.7 %) cases the treatment was found unsatisfactory. Eighty-six (93.5 %) patients with adverse events continued Glyciphon ointment therapy. The relapse rate after local drug therapy was 4.4 %, indicating its high efficacy and good tolerance. According to the study, most patients required 1 treatment course with 1 package of Glyciphon. Total cost of the treatment is approximately 17,000 rubles. Total budget expenditures are estimated at 1 billion 190 million rubles. Local BCC therapy with Glyciphon comparing to surgery may save more than 1 billion rubles for the state budget.Conclusion. Local chemotherapy with 30 % Glyciphon ointment is an effective and safe method to treat BCC. Its use increases treatment availability for patients and can significantly reduce federal expenditures.